(untitled) (FULAFIA IAC Book of Proceedings, 2024)
Malaria still remains a health challenge in Nigeria and even though a lot of efforts have been made in controlling the rate of infection, several people are still at risk of the parasitic infection. This study determined the prevalence of malaria parasites among patients attending General Hospital Wuse, Abuja. The sample population included 232 out-patients who presented with symptoms of malaria infections at the hospital. Five milliliters (5mls) of blood was collected from the patient into well labeled ethylenediaminetetraacetic acid tubes and malaria parasite was examined using a microscopy. Chi square (χ2) test was used for data analysis at 0.05 probability level. The overall prevalence of malaria was 45.7%. There was significant difference in the prevalence of malaria between microscopy and RDTs (p<0.005). Age groups 21 – 30 had the highest prevalence of 29.2%, followed by 17.9% in 41 – 50 age groups. The least prevalence of 4.7% was seen in age groups 51 and above. Patients who sleep under mosquito net (22.6%) had less prevalence compared to 77.3% recorded among patients that did not sleep under mosquito treated net. Prevalence of malaria parasites based on gender recorded in this study is higher in females 71 (66.9%) than males 35 (33.0%). A malaria prevalence rate of 45.7% is considered high and should be a cause for significant concern and urgent efforts of control strategies in the affected Area.